The Influence of ESG Performance and Financial Distress on Earnings Management Practices - Rifda Nadifah (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
The findings of the study indicate that there is a considerable relationship between ESG performance, financial distress, and earnings management. The mean ESG performance value is 0.59, whereas the mean financial distress value is 8.30, suggesting a favorable financial state. Within the realm of earnings management, corporations operating in the energy and oil and gas sectors engage in the practice of manipulating their financial results, resulting in a reduction of profits by 16% and 76%, respectively. A study was undertaken to investigate the impact of ESG performance and the financial crisis on earnings management using multiple linear regression analysis. The findings indicate a negative relationship between greater environmental, social, and governance (ESG) performance scores and earnings management. Additionally, improved social performance is associated with a decrease in loan loss provisions, resulting in enhanced earnings and a reduction in loss avoidance activities. A financial crisis can have an impact on earnings management, as organizations may engage in strategies to enhance their financial accounts to attract investors and bolster profits.